Initial Molecular Response at 3 Months May Predict Both Response and Event-Free Survival at 24 Months in Imatinib-Resistant or -Intolerant Patients With Philadelphia Chromosome-Positive Chronic Myeloid Leukemia in Chronic Phase Treated With Nilotinib - Branford, Susan; Müller, Martin Christian (Journal of clinical oncology, 2012)
Purpose The association between initial molecular response and longer-term outcomes with nilotinib was examined. Patients and Methods Patients with imatinib-resistant or -intolerant chronic myeloid leukemia in chronic phase from the phase II nilotinib registration study with available postbaseline BCR-ABL1 transcript assessments were included (N = 237). Results BCR-ABL1 transcript levels (International Scale [IS]) at 3 months correlated with complete cytogenetic response (CCyR) by 24 months. Patients with BCR-ABL1 (IS) of > 1% to ≤ 10% at 3 months with nilotinib had higher cumulative incidence of CCyR by 24 months than patients with BCR-ABL1 (IS) of > 10% (53% v 16%). BCR-ABL1 (IS) at 3 months predicted major molecular response (MMR) by 24 months. Cumulative incidence of MMR by 24 months for patients with BCR-ABL1 (IS) of > 0.1% to ≤ 1%, > 1% to ≤ 10%, and > 10% was 65%, 27%, and 9%, respectively. These differences were observed for patients with or without baseline BCR-ABL1 mutations and for those with imatinib resistance or intolerance. Estimated event-free survival (EFS) rates at 24 months decreased with higher transcript levels at 3 months; patients with BCR-ABL1 (IS) of ≤ 1% had an estimated 24-month EFS rate of 82%, compared with 70% for patients with BCR-ABL1 (IS) of > 1% to ≤ 10% and 48% for patients with BCR-ABL1 (IS) of > 10%. Conclusion Patients with BCR-ABL1 (IS) of > 10% at 3 months had a lower cumulative incidence of CCyR and MMR and lower rates of EFS versus patients with BCR-ABL1 (IS) of ≤ 10%. Prospective studies may determine whether close monitoring or alternative therapies are warranted for patients with minimal initial molecular response.